Identifikasi Cendawan Entomopatogen Lokal dan Tingkat Patogenitasnya Terhadap Hama Wereng Hijau (Nephotettix virescens Distant.) Vektor Virus Tungro pada Tanaman Padi Sawah di Kabupaten Donggala - Rosmini Rosmini; Sri Anjar Lasmini (Agroland: Jurnal Ilmu-ilmu Pertanian, 2010)
The objective of this research was to identify entomopathogenic fungi associated with green leafhopper (Nephotetix virescens) and to determine its virulence toward N. viresnes mortality. The indicators of pathogenicity were symptoms, time of symptom appeared, and mortality of green leafhopper after inoculation of the entomopathogenic fungi. The research was conducted in three phases. The first phase was collecting green leafhopper infected by entomopathogenic fungi in the field. The second phase was isolation, inoculation, and re-isolation of entomopathogenic fungi from the infected green leafhopper (wereng). The third was pathogenicity assay conducted in the Laboratory of Plant Pest and Disease, Faculty of Agriculture, Tadulako University. The research was conducted for four months from February to May 2010. Five isolates of entomopathogenic fungi were collected in Donggala Regency: Metharizium sp., Asperigillus sp., Beauveria sp., Cladosporium sp. and Fusarium sp. Two isolates were found potential as entomopathogenic fungi: Metarhizium sp. and Beauveria sp. Mortality of nimpha green leafhopper (wereng hijau) caused by both fungi were 80.75%, and 80.25% respectively.